A Rash Decision. The Hazards of the Wrongful Use of Adrenaline - Coutinho Cruz, M (2018)
Anaphylaxis is life-threatening and should be addressed urgently. Its treatment is not without side effects and an accurate diagnosis must be made to prevent potential harm by the wrongful use of medication. A 46-year-old woman with hypertension treated with angiotensin converting enzyme inhibitor (ACEI) presented to the emergency department with non-pitting oedema of the face and limbs. A hasty diagnosis of anaphylaxis was made and intravenous adrenaline administered. The patient developed a myocardial infarction caused by coronary artery spasm that required invasive intervention. The initial clinical picture was resolved when the ACEI was discontinued unmasking a case of ACEI-induced angioedema. The correct differentiation of these two apparently similar clinical entities is of utmost importance in the management of emergency department patients.